“Animanazo”. Song and memories. Cultural expressions and movements in the reconstruction of the past inside a north Argentinian town - Villagrán, Andrea Jimena; López, Irene (Revista de Antropología Social, 2016)
This article analyses the context of production and local situations of appropriation and resignification related to the folk song “Fire on Animaná” as well as the request and mobilization (“The animanazo”) provoked by this song in order to examine different mechanisms and foundations by which a population connect with an event from its community past, identifying with this and taking it in a specific way. In this article we combine discourse analysis of the song and of interviews to participants in this event with the reconstruction —through ethnographic observation— of how to use this song.